Beliefs about health and illness: a comparison between Ugandan men and women living with Diabetes Mellitus - Hjelm, K.; Nambozi, G. (International Nursing Review, 2008)
Background: The diabetes mellitus (DM) pandemic greatly affects developing countries. Self-care is an important part of management, guided by beliefs about health and illness. Dissimilarities in health-related behaviour in men and women have been described but not comparisons of their beliefs about health and illness. Aim: To explore beliefs about health and illness that might affect self-care practice and healthcare-seeking behaviour in men and women with DM in Uganda. Methods: This was an exploratory study with a consecutive sample from an outpatient diabetes clinic at a university hospital. Semi-structured interviews were conducted with 15 women and 10 men aged 21–70 years. Data analysis was conducted by qualitative content analysis. Findings: Men’s and women’s beliefs about health and illness indicated limited knowledge about the body and DM. Dissimilar were men’s focus on socio-economic factors, particularly affordability of drugs, sexual function and lifestyle, while women valued well-being, support in daily life and household activities and had a higher risk-awareness of DM. Irrespective of gender, limited self-care measures were used, and health professionals were consulted about health problems. Conclusion: Similarities and dissimilarities were found between men and women in beliefs about health and illness that affect self-care practice and healthcare seeking. Underlying living conditions, with different gender roles, appear to determine the beliefs about health and illness, which are based on individual knowledge. Measures to increase knowledge about DM are urgently needed in Uganda. In diabetes care, it is important to search for individual beliefs and consider gender and living conditions.
Keywords: Care-Seeking Behaviour; Diabetes Mellitus; Gender; Health/Illness Beliefs; Self-Care; Uganda